Analysis of the Implementation of Non-Smoking Area Policy in Madiun Middle Schools and High Schools - Fariz Kahendra; Bagoes Bagoes Widjanarko; Farid Agushybana (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2023)
Indonesia became the second largest cigarette market in the world. Based on the 2018 Riskesdas data, the prevalence of smokers aged over 15 years was 33.8 percent Based on Madiun Regency Regional Regulation Number 10 of 2020 Concerning Non-Smoking Areas. The aim of this research is to find out about smoking-free area policies in junior high schools and high schools in Madiun City. The implementation of this research was carried out in January-February 2023 in the Madiun City Middle School and High School environment with the research subjects being 35 school principals or persons in charge of smoking-free areas in Middle and High Schools in Madiun City. The sampling procedure was proportional random sampling. collection of research data with primary data collected using a questionnaire Implementation of policies according to van horn and van meter theory. Data analysis in this study is multivariate analysis with multiple regression tests..The results showed that there was influence from the social, economic and political environment (p value 0.012), there was an influence on the implementor's position (p value 0.016), and there was no influence on the character of the executing agent (p value 0.837) in the Madiun City Middle School and High School environment. There is a need for support from the Education Office and the school itself, such as providing visual media as facilities and infrastructure that support the implementation of smoking-free areas and continuously socialize the dangers of smoking at every school meeting and ceremonial activities or morning assembly. This will play a role in making a policy easier to remember in the school community. Keyword: Implementation, No-Smoking Areas, Policy, Schools, Smoking